Creativity and Styles of Teaching of Hindi Medium and English Medium School Teachers : A Comparative Study - Jha, J. S.; Rastogi, Praveen (INDIAN EDUCATIONAL REVIEW, 2014)
Two basic types of schools are found in India-English Medium and Hindi Medium schools. The former are generally preferred by the elite class of our society. English Medium Schools are often labeled as ‘better’ when compared with their Hindi Medium counterparts. They are expected to use more modern methods and techniques to teach the students, where as Hindi Medium Schools are generally anticipated to continue the age old traditional methods of teaching. To find out the truth of this paradoxical situation, a humble attemp was made to study the creativity and styles of teaching of Hindi Medium and English Medium School teachers; an endeavor was made to find out the relation between teachers’ creativity and their styles of teaching. Creativity and style of teaching of a teacher are the two eminent factors that distinguish one teacher from another. Thus, the difference between the two medium of schools could be studied on the basis of these two qualities of the teachers teaching in relevant institutions. The sample for the study comprised 260 teachers selected randomly from various Hindi Medium and English Medium Schools private as well as government. In order to achieve the objectives, tests of teaching and creativity were used. The study revealed that the teachers on Hindi Medium and English Medium Schools significantly differed in their styles of teaching but they did not show any significant difference in their creativity. The style of teaching of teachers of both mediums was not found significantly related with their creativity. The study concluded that every teachers, irrespective of his sex, medium of instruction or style of teaching (traditional or objective based) has to be creative and innovative to achieve his/her teaching aims. The study also makes suggestions for further researches to validate and generalise the results of the present research work.